Bandwidth Optimization of Mikrotik-Based School Wi-Fi Networks Using Queue Tree and QoS - Rudiyanto, Randi; Asri, Sri Dianing (Journal of Computer Science and Informatics Engineering, 2025)
The rapid development of technology in the era of the Fourth Industrial Revolution has driven humanity and various sectors to quickly adapt, including internet network infrastructure in educational institutions. The internet has become the backbone in supporting smooth administrative processes and learning activities. However, the high number of users often leads to a decline in connection quality, such as slow data access and increased delay. To address this issue, an appropriate bandwidth management method is required to ensure a more balanced and efficient distribution of connections.This study employs the MikroTik RB450Gx4 device with the Queue Tree method and Quality of Service (QoS) to proportionally distribute bandwidth. Testing was conducted by measuring network performance parameters, including throughput, latency, packet loss, and jitter, both before and after the implementation of the method.The results indicate an average throughput increase of 27%, a decrease in latency from 60 ms to 40 ms, a reduction in packet loss from 5% to below 1%, and more stable jitter maintained under 5 ms. These improvements demonstrate that implementing bandwidth management based on Queue Tree and QoS can significantly enhance connection quality. In conclusion this method can effectively support operational activities and learning processes within the school environment